My new home: study protocol for a prospective cohort study on the long-term personality development and short-term processes during transitions into nursing homes - Sun, Yang; Wrzus, Cornelia (BMC geriatrics, 2025)
Personality is a crucial predictor of many life outcomes, including successful ageing. The proportion of nursing home residents is increasing annually among older populations. Relocations to nursing homes affect multiple aspects of older people’s lives, including their living environment, social interactions, and daily arrangements, which may indirectly affect their personality development. However, there is currently a lack of comprehensive assessments of how transitioning into a nursing home impacts personality development among older adults. This knowledge gap impedes our understanding of personality development in nursing home residents and also prevents our gaining insights into the related mechanisms and influences on personality development in later adulthood.
Veröffentlicht: 19. August 2025
Gesehen am 09.01.2026